Low prevalence of fibrosis in thalassemia major assessed by late gadolinium enhancement cardiovascular magnetic resonance - Kirk, Paul (BioMed Central, 2011)
BACKGROUND: Heart failure remains a major cause of mortality in thalassaemia major. The possible role of cardiac fibrosis in thalassemia major in the genesis of heart failure is not clear. It is also unclear whether cardiac fibrosis might arise as a result of heart failure. METHODS: We studied 45 patients with thalassaemia major who had a wide range of current cardiac iron loading and included patients with prior and current heart failure. Myocardial iron was measured using T2* cardiovascular magnetic resonance (CMR), and following this, late gadolinium enhancement (LGE) was used to determine the presence of macroscopic myocardial fibrosis. RESULTS: The median myocardial T2* in all patients was 22.6 ms (range 5.3-58.8 ms). Fibrosis was detected in only one patient, whose myocardial T2* was 20.1 ms and left ventricular ejection fraction 57%. No fibrosis was identified in 5 patients with a history of heart failure with full recovery, in 3 patients with current left ventricular dysfunction undergoing treatment, or in 18 patients with myocardial iron loading with cardiacT2* < 20 ms at the time of scan. CONCLUSION: This study shows that macroscopic myocardial fibrosis is uncommon in thalassemia major across a broad spectrum of myocardial iron loading. Importantly, there was no macroscopic fibrosis in patients with current or prior heart failure, or in patients with myocardial iron loading without heart failure. Therefore if myocardial fibrosis indeed contributes to myocardial dysfunction in thalassemia, our data combined with the knowledge that the myocardial dysfunction of iron overload can be reversed, indicates that any such fibrosis would need to be both microscopic and reversible.